A Review of Musical Content Creativity in the Vocal Groove Community - Adelya Annisa Marfirasari (Repertoar, 2026)
This study aims to describe in depth the various stages of the creative process undertaken by Vocal Groove in creating music content, as well as to analyze creative solutions to overcome constraints in creating music content.  This study uses qualitative methods, with data collection based on observation of Vocal Groove content on TikTok, in-depth interviews with members and the founder of the Vocal Groove community, and supporting documentation.  This research examines the creative process of the Vocal Groove community in creating music content on TikTok, focusing on the case study " Never Enough ." This research uses Graham Wallas' four-stage theory of creativity, namely preparation, incubation, illumination, and verification.  The results show that the creative process is iterative.  Various obstacles, such as member absences, differences in understanding the song, and technical problems, are overcome through creative solutions such as role-sharing, independent practice, group practice, and team collaboration.  Despite limitations, Vocal Groove is still able to produce engaging, high-quality music content through collective work and social media adaptation.